Arctic and Antarctic ozone layer observations: chemical and dynamical aspects of variability and long-term changes in the polar stratosphere - Rex, Markus; Dethloff, Klaus; Handorf, Dörthe; Herber, Andreas; Lehmann, Ralph; Neuber, Roland; Notholt, Justus; Rinke, Annette; von der Gathen, Peter; Weisheimer, Antje; Gernandt, Hartwig (Polar Research, 2000)
The altitude dependent variability of ozone in the polar stratosphere is regularly observed by balloon-borne ozonesonde observations at Neumayer Station (70°S) in the Antarctic and at Koldewey Station (79°N) in the Arctic. The reasons for observed seasonal and interannual variability and long-term changes are discussed. Differences between the hemispheres are identified and discussed in light of differing dynamical and chemical conditions. Since the mid- 1980s, rapid chemical ozone loss has been recorded in the lower Antarctic stratosphere during the spring season. Using coordinated ozone soundings in some Arctic winters, similar chemical ozone loss rates have been detected related to periods of low temperatures. The currently observed cooling trend of the stratosphere, potentially caused by the increase of anthropogenic greenhouse gases, may further strengthen chemical ozone removal in the Arctic. However, the role of internal climate oscillations in observed temperature trends is still uncertain. First results of a 10000 year integration of a low order climate model indicate significant internal climate variability. on decadal time scales, that may alter the effect of increasing levels of greenhouse gases in the polar stratosphere.
Keywords: Antarktis; drivhusgasser; klimaendringer; klimagasser; meteorologi; observasjoner; ozonlaget; polarområdene; stratosfæren

The impact of greenhouse gases and halogenated species on future solar UV radiation doses - Taalas, Petteri; Kaurola, Jussi; Kylling, Arve; Shindell, Drew; Sausen, Robert; Dameris, Martin; Grewe, Volker; Herman, Jay; Damski, Juhani; Steil, Benedikt (Geophysical Research Letters, 2000)
The future development of stratospheric ozone layer depends on the concentration of chlorine and bromine containing species. The stratosphere is also expected to be affected by future enhanced concentrations of greenhouse gases. These result in a cooling of the winter polar stratosphere and to more stable polar vortices which leads to enhanced chemical depletion and reduced transport of ozone into high latitudes. One of the driving forces behind the interest in stratospheric ozone is the impact of ozone on solar UV-B radiation. In this study UV scenarios have been constructed based on ozone predictions from the chemistry-climate model runs carried out by GISS, UKMO and DLR. Since cloudiness, albedo and terrain height are also important factors, climatological values of these quantities are taken into account in the UV calculations. Relative to 1979–92 conditions, for the 2010–2020 time period the GISS model results indicate a springtime enhancement of erythemal UV doses of up to 90% in the 60–90 °N region and an enhancement of 100% in the 60–90 °S region. The corresponding maximum increases in the annual Northern Hemispheric UV doses are estimated to be 14% in 2010–20, and 2% in 2040–50. In the Southern Hemisphere 40% enhancement is expected during 2010–20 and 27% during 2040–50.
Keywords: Antarktis; UV-stråling; drivhusgasser; klimaendringer; klimatologi; ozonlaget; polarområdene; ultrafiolett stråling